2012
DOI: 10.1037/a0027383
|View full text |Cite
|
Sign up to set email alerts
|

Age-based differences in treatment outcome among alcohol-dependent women.

Abstract: The literature suggests that women are at higher risk for negative consequences from alcohol use than men and that these risks are compounded by age. The current study investigated how alcohol dependent women from different age groups might differ in terms of baseline functioning and treatment response. The sample consisted of 181 participants drawn from 2 randomized clinical trials of cognitive behavioral treatments for alcohol dependent women. Demographic and psychopathology data were obtained at baseline us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The later age of onset of substance dependence in middle-aged adults compared to younger adults in this analysis is also consistent with our previous dataset (Kalapatapu et al, 2011) and other studies (Al-Otaiba et al, 2012; Arndt et al, 2002). This difference may be due to biased recall, where younger adults were more likely to remember an earlier age of onset because it is more recent due to their younger age.…”
Section: Discussionsupporting
confidence: 93%
“…The later age of onset of substance dependence in middle-aged adults compared to younger adults in this analysis is also consistent with our previous dataset (Kalapatapu et al, 2011) and other studies (Al-Otaiba et al, 2012; Arndt et al, 2002). This difference may be due to biased recall, where younger adults were more likely to remember an earlier age of onset because it is more recent due to their younger age.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, although not reviewed in detail in this manuscript, there are other key variables that interact with sex/gender, such as socioeconomic status (E. O. Johnson & Novak, 2009), age (Al-Otaiba, Epstein, McCrady, & Cook, 2012), race/ethnicity (Guerrero, Marsh, Cao, Shin, & Andrews, 2014; Montgomery, Burlew, Kosinski, & Forcehimes, 2011), and sexual orientation (Medley et al, 2016). Specifically, these groups differ with respect to access to substances, risk for problematic substance use, and access to substances; the nature of these differences and their implications for treatment are not yet well-characterized.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study reported older women to have relatively less severe substance abuse and better social networking and treatment outcome compared to younger women. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%